The German Reformation: the essential readings - Dixon, C. Scott (Blackwell essential readings in history, 1999)
This is a comprehensive introduction to the Pietist theologians of the seventeenth and eighteenth centuries in Puritan England, Pietist Europe and Colonial America. It demonstrates the influence that Pietism had on the religious, cultural and social life of the time. It explores the lasting effects Pietism has had on modern theology and modern culture. It presents both Protestant and Catholic theologians in Puritan England, Pietist Europe and Colonial America. It focuses on women as well as men. It features up-to-date research and commentary by an international group of leading scholars.